FedSeq: Personalized Federated Learning via Sequential Layer Expansion in Representation Learning - Jae Won Jang; Bong Jun Choi (Applied Sciences, 2024)
Federated learning ensures the privacy of clients by conducting distributed training on individual client devices and sharing only the model weights with a central server. However, in real-world scenarios, especially in IoT scenarios where devices have varying capabilities and data heterogeneity exists among IoT clients, appropriate personalization methods are necessary. In this paper, this work aims to address this heterogeneity using a form of parameter decoupling known as representation learning. Representation learning divides deep learning models into ‘base’ and ‘head’ components. The base component, capturing common features across all clients, is shared with the server, while the head component, capturing unique features specific to individual clients, remains local. This work proposes a new representation learning-based approach, named FedSeq, that suggests decoupling the entire deep learning model into more densely divided parts with the application of suitable scheduling methods, which can benefit not only data heterogeneity but also class heterogeneity. FedSeq has two different layer scheduling approaches, namely forward (Vanilla) and backward (Anti), in the context of data and class heterogeneity among clients. Our experimental results show that FedSeq, when compared to existing personalized federated learning algorithms, achieves increased accuracy, especially under challenging conditions, while reducing computation costs. The study introduces a novel personalized federated learning approach that integrates sequential layer expansion and dynamic scheduling methods, demonstrating a 7.31% improvement in classification accuracy on the CIFAR-100 dataset and a 4.1% improvement on the Tiny-ImageNet dataset compared to existing methods, while also reducing computation costs by up to 15%. Furthermore, Anti Scheduling achieves a computational efficiency improvement of 3.91% compared to FedAvg and 3.06% compared to FedBABU, while Vanilla Scheduling achieves a significant efficiency improvement of 63.93% compared to FedAvg and 63.61% compared to FedBABU.